Cross-border reserve markets: network constraints in cross-border reserve procurement. (February 2018) - Van den Bergh, Kenneth; Bruninx, Kenneth; Delarue, Erik
Abstract: Cross-border reserve markets—the procurement and activation of reserves in one control area to maintain system balance in another control area—can lead to increased cost-efficiency and reliability. However, network constraints impose limits on cross-border reserve coordination. Transmission capacity allocation in the reserve market is a complex problem, as it happens under uncertainty and interferes with transmission capacity allocation in energy markets. This paper studies network constraints in the reserve procurement phase, by means of a simulation model and scenario analysis. Three different approaches are proposed and evaluated based on a case study of the Central Western European electricity system. Towards this aim, a dedicated model is developed to simulate the day-ahead energy market, the day-ahead reserve procurement and the real-time reserve activation. In a case study of the Central Western European power system, we show that the best reserve market outcome—weighing cost-efficiency and system reliability—is obtained when reserve activation scenarios are considered in the procurement phase. Policy makers should design, in close cooperation with regulators and system operators, efficient and robust transmission capacity allocation procedures for cross-border reserve markets. This paper can help them to do so as it demonstrates the impact of transmission capacity allocation on cross-border reserve markets. Highlights: We present a novel model for cross-border reserve procurement. The model is applied to a case study of Central-Western Europe. The analysis quantifies the cost efficiency gains of cross-border reserve markets. Significant operating cost savings are demonstrated for Central-Western Europe. The importance of network constraints in cross-border reserve procurement is shown.